Kontruksi Identitas Anak Pada Keluraga Amalgamasi Etnis Melayu dan Jawa di Kelurahan Tanjung Uma Kota Batam Tahun 2022 - Permata, Bunga Dinda; Syafrini, Delmira; Fitrisia, Azmi; Erianjoni, Erianjoni (Jurnal Kronologi, 2024)
This article discusses how the construction of children's identities in families with amalgamated marriages in the Malay and Javanese ethnic groups in Tanjung Uma Village, Batam City. This study is interesting because the Malay and Javanese ethnic groups are ethnic groups that have different cultural characteristics, so that adjustments are needed in the formation of cultural identities in family members. This study uses the Social Construction theory of Peter L. Berger. The research method used in this study is the historical method which goes through four stages, namely: data collection or heuristics, criticism, interpretation and writing. The data collection process is carried out first by heuristics, where researchers collect relevant historical sources by observing how families with amalgamated marriages of the Malay and Javanese ethnic groups live. The second stage is criticism, at this stage the researcher conducts criticism by assessing the authenticity of documents, the physical condition of the archives of amalgamated marriage data in Tanjung Uma Village. The third stage, the interpretation stage, researchers use a relevant theoretical framework on the formation of children's identities in amalgamated marriage families. The fourth stage of Historiography is presenting the results of the study through the stages of sources, data, and evidence, in this case the researcher took data from Tanjung Uma Village regarding the amalgamation marriage families of Malay and Javanese ethnicities. The research findings show that there are three main factors in the formation of the cultural identity of children from amalgamation marriage families of Malay and Javanese ethnicities in Tanjung Uma Village. First, the locality factor where the dominant Malay culture in Tanjung Uma greatly influences the cultural identity of children. Second, the role of parents in internalizing cultural values ​​to their children. Parents act as the main socialization agents who introduce and teach both cultures. Third, cultural adjustment in amalgamation marriage families of Malay and Javanese ethnicities in Tanjung Uma Village shows a process of adjustment, especially the dominant Malay culture as the local culture.